Hubungan Kekerabatan Bahasa Pesisir Pasar, Kampung, dan Sorkam (Kajian Linguistik Historis Komparatif) - Siti Aisyah; Dwi Widayati (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
This study was focused on historical-comparative linguistics and discussed the language kinship among Pesisir Pasar, Pesisir Kampung, and Pesisir Sorkam languages where the different languages were in the Sibolga district of Centre Tapanuli in North Sumatera. The populations and samples were taken from the local people of each district. The researchers aimed to find out the sameness of the different languages’ vocabularies. This study used descriptive quantitative research by visiting the location of each language and interviewing the local informant of each district. This study used the numbers to find out the average in percent so that the relationship The findings of this research were 60 % (sixty percent) and it meant that the different languages were so close to each other because they were in one area of Centre Tapanuli. It happened because there were 119 same words in the vocabulary. The identic couples were 89 words and 30 words of correspondence phonemics. In this correspondence phonemic, there were a few different letters or one letter, one of them was the word bunuh (Pasar language), bunoh (Kampung language) and buno (Sorkam language).